Glucocorticoid Signaling and Bone Biology - Komori, T. (Hormone and Metabolic Research, 2016)
Since glucocorticoids remain an effective therapeutic option for the treatment of many inflammatory and autoimmune diseases, glucocorticoid-induced osteoporosis is the most common form of secondary osteoporosis. Fractures may occur in as many as 30–50% of patients receiving chronic glucocorticoid therapy. Under physiological conditions, glucocorticoids are required for normal bone development due to their regulation of osteoblast differentiation, possibly via the Wnt/β-catenin pathway and TSC22D3. However, serum levels of endogenous corticosterone are elevated in aged mice and glucocorticoids exert negative effects on the survival of osteoblasts and osteocytes as well as angiogenesis. Glucocorticoid treatments impair bone formation and enhance bone resorption. Excess glucocorticoids induce osteoblast and osteocyte apoptosis by increasing pro-apoptotic molecules, reactive oxygen species, and endoplasmic reticulum stress and suppressing the Wnt/β-catenin pathway. Autophagy protects osteocytes from glucocorticoid-induced apoptosis, but passed some threshold, the process of autophagy leads the cells to apoptosis. Excess glucocorticoids impair osteoblastogenesis by inducing Wnt antagonists, including Dkk1, Sost, and sFRP-1. However, the findings are controversial and the involvement of Wnt antagonists requires further study. Excess glucocorticoids reduce the phosphorylation of Akt and GSK3β, which enhances the degradation of β-catenin. Excess glucocorticoids have been shown to modulate the expression of miRNAs, including miR-29a, miR-34a-5p, and miR-199a-5p, which regulate the proliferation and differentiation of osteoblast lineage cells. Excess glucocorticoids also enhance bone resorption by reducing OPG expression, increasing Rankl expression and reactive oxygen species, and prolonging the life span of osteoclasts; however, they also suppress the bone-degrading capacity of osteoclasts by disturbing the organization of the cytoskeleton.
Keywords: apoptosis; autophagy; wnt; osteoblast; osteoclast; OPG